Cutaneous metastasis of renal cell carcinoma: Fine needle aspiration provides rapid diagnosis. Issue 1 (14th December 2018) - Mirza, Rusella; Ellsworth, Steven; King, Judy; Sangster, Guillermo; Shi, Mingxia
Key Clinical Message: The diagnosis of cutaneous metastasis of renal cell carcinoma is challenging in a young person in absence of a prior history of cancer. In such situation, fine needle aspiration alone as a minimally invasive procedure can provide rapid, accurate and cost effective diagnosis, even in case of unknown primary. Abstract : The diagnosis of cutaneous metastasis of renal cell carcinoma is challenging in a young person in absence of a prior history of cancer. In such situation, fine needle aspiration alone as a minimally invasive procedure can provide rapid, accurate and cost effective diagnosis, even in case of unknown primary.